1992
DOI: 10.1021/ja00034a011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 chemical shift tensors in aromatic compounds. 3. Phenanthrene and triphenylene

Abstract: perfine structure indicative of an exchange-coupled manganese center in signals near g = 4 in ammonia-treated PS II preparations.In addition, Baumgarten et al.34 measured light-induced changes in the magnetic susceptibility of fluoride-treated PS II preparations, which exhibit an altered EPR signal at g -4.2 in the S2 state,7•35 that they interpreted as evidence of a magnetically coupled site. These chemically inhibited preparations, although giving rise to altered EPR properties, have been considered as possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 2 publications
5
19
0
Order By: Relevance
“…The principal values and tensor orientation data obtained for EC, ETTC, DPC, ETTC, and DMTTC in this study complement the previous data on the ionic potassium carbonates and thiocarbonates [1], the PAHs [7,[32][33][34][35][36][37], and the C/TC compounds studied by Kirby et al [8]. Figure 5 compares the bonding structure of the planar carbonate and thiocarbonate groups in the neutral dialkyl compounds with the bonding structure of the planar groups in the monoalkyl carbonate and thiocarbonate anions.…”
Section: Chemical Shift Tensor Orientationssupporting
confidence: 81%
“…The principal values and tensor orientation data obtained for EC, ETTC, DPC, ETTC, and DMTTC in this study complement the previous data on the ionic potassium carbonates and thiocarbonates [1], the PAHs [7,[32][33][34][35][36][37], and the C/TC compounds studied by Kirby et al [8]. Figure 5 compares the bonding structure of the planar carbonate and thiocarbonate groups in the neutral dialkyl compounds with the bonding structure of the planar groups in the monoalkyl carbonate and thiocarbonate anions.…”
Section: Chemical Shift Tensor Orientationssupporting
confidence: 81%
“…In perylene the averaged δ 33 for the outer β positions and inner β positions is 10.6 and 8.5 ppm, respectively, and this modest 2 ppm lower frequency shift on δ 33 of the inner β positions can be attributed to the steric interactions between the intramolecular bay hydrogens, as is observed for the α positions in phenanthrene . A value of 11−14 ppm has been observed for δ 33 shift components of carbons β to a bridgehead carbon in naphthalene, 1,2,3,6,7,8-hexahydropyrene, 1,4,5,8-tetramethylnaphthalene, and acenaphthene …”
Section: Discussionmentioning
confidence: 79%
“…This perylene study is a natural extension to the previous work on 13 C chemical shift tensors in representative polycyclic aromatic hydrocarbons (PAH), e.g., pyrene, naphthalene, phenanthrene, substituted naphthalene compounds, and acenaphthene . Moreover, perylene is one of the simplest PAH where the Kekule structures predict the confinement of the π-electrons to the naphthalene residues, therefore this study of its 13 C chemical shift tensors provides further insight into the localization−delocalization aspect of π-electron structure.…”
Section: Introductionmentioning
confidence: 72%
“…Qualitative rules for the 13 C chemical shift tensor orientations in condensed PAHs have been established [34][35][36][37][38][39][40]. In these compounds, it was found that the d 33 component is always oriented perpendicular to the s-electron planes of the molecules, and that d 11 and d 22 are always the two in-plane components.…”
Section: Comparison With Polyaromatic Hydrocarbons (Pahs)mentioning
confidence: 99%